(untitled) (translation. a transdisciplinary journal, 2022)
The issue will explore the different processes of translation that occur in the continuous negotiation of and in spaces and places. The initial idea is that all translation takes place in spaces and is both conditioned by space and able to promote or provoke changes in the perception and the use of spaces.